Slow Tourism as a Cultural Safeguard: Ethno Ecotourism–Based Visitor Education in Saba Budaya Baduy - Triandi Pradana; Lytiana Natalie (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2026)
Mass tourism has generated significant economic benefits but also triggered environmental degradation, cultural commodification, and social pressures on host communities, particularly in indigenous territories. In response to these challenges, this study examines slow tourism as a cultural safeguarding mechanism through an ethno-ecotourism based visitor education model in Saba Budaya Baduy, Indonesia. Employing a qualitative methodology grounded in the Design Thinking framework, data were collected through in-depth interviews, participant observation, and document analysis involving customary leaders (Puun and Jaro), local guides, government officials, residents, and visitors. The findings show that visitor education transforms awareness, emotional engagement, and behavior in accordance with Baduy customary law (pikukuh). The saba budaya concept, regulated by Kanekes Village Regulation No. 1 of 2007, reframes tourism as a respectful cultural visit rather than a commercial activity. The zoning system between Outer and Inner Baduy also supports a structured, community-managed visitation model aligned with slow tourism principles. However, limited visitor awareness and insufficient dissemination of rules remain key challenges. This study concludes that slow tourism based on indigenous governance and ethno-ecotourism principles can strengthen cultural resilience if visitor education is enhanced and community authority is consistently maintained in tourism planning, management, and decision-making.